Health care provider decision-making around prenatal substance use reporting. (1st August 2022) - Roberts, Sarah CM; Zaugg, Claudia; Martinez, Noelle
Abstract: Background: Recent research has found that harms related to alcohol and/or drug (AOD) use during pregnancy are not limited to those associated with use itself; harms also result from policies and health care practices adopted in response, including reporting to Child Protective Services (CPS). This study sought to understand factors that influence health care providers' reporting practices. Methods: We conducted 37 semi-structured interviews with hospital-based obstetricians/gynecologists, family medicine physicians, and emergency department physicians, focused on experiences with reporting pregnant/birthing people with AOD to government authorities. We deductively applied an implementation science framework, the Theoretical Domains Framework (TDF) to identify the relevant domains and then inductively coded within domains to identify sub-themes. Results: Most participants saw reporting as someone else's job, primarily social workers. While a few participants associated reporting with increased connection to services, many participants expressed awareness of negative consequences associated with reporting. Nonetheless, participants were much more concerned about potential harms to the baby associated with not reporting and expressed considerable anxiety about these harms occurring if a report was not made. While a few participants described making reporting decisions themselves, most described interpersonal, hospital-level, and state policy-level factors that constrained their decision-making. Conclusions: Many of the factors that influence physician decision-making in reporting pregnant/birthing people who use AOD to CPS are outside the control of individual physicians and require social, structural, and policy changes. Those that are individual-focused involve intense emotions and thus are unlikely to be influenced by solely didactic cognitive-focused trainings. Highlights: Most physicians saw CPS reporting as someone else's job, primarily social workers. A few physicians saw CPS reporting as connecting people to services. Many physicians were aware of negative consequences of CPS reporting. Physicians were more worried about potential harms to babies if CPS reports not made. Interpersonal, organizational, and policy factors constrain reporting decisions.